Antimicrobial susceptibility of bacteremic isolates of Salmonella enterica serovar typhi and paratyphi infection in Pakistan from 2017-2020 - Fasih, Fatima; Fatima, Ambreen; Baig, Samina; Naseem , Saima; Tauheed, Muhammad Moazzam; Gohar, Hareem (Journal of the Pakistan Medical Association, 2023)
Objective: To find out the antibacterial susceptibility pattern of bacteraemia isolates of Salmonella enterica serovar typhi and paratyphi. Method: The retrospective descriptive observational study was conducted at the Microbiology section of Dow Diagnostic Research and Reference Laboratory, and comprised blood culture reports from January 1, 2017, to Dec 30, 2020, which were screened for the presence of Salmonella typhi and paratyphi growth The frequency of the isolates and their antibiotic resistance patterns were analysed. Data was analysed using SPSS 20. Results: Of the 174,190 blood culture samples, 62,709(36%) were positive for bacterial growth. Salmonella were isolated in 8,689(13.8%) samples of which 8,041(92.5%) were Salmonella typhi, 529(6%) were Salmonella paratyphi A and 119(1.3%) were Salmonella paratyphi B. There was a drastic increase in resistance to third-generation cephalosporin in Salmonella typhi from 71(12.8%) in 2017 to 1,420(71%) in 2018, 2,850(74.6%) in 2019 and 1,251(77%) in 2020. All isolates were sensitive to meropenem and azithromycin. Conclusion: A high number of extensively drug-resistant typhoid cases due to Salmonella typhi were found. All isolates were sensitive to meropenem and azithromycin. Key Words: Salmonella typhi, Multidrug resistance, Extensively drug-resistant.